Influence of weekly workload on physical, biochemical and psychological characteristics in professional rugby union players over a competitive season - Dubois, R.; Lyons, M.; Paillard, T.; Maurelli, O.; Prioux, J. (The Journal of Strength and Conditioning Research, 2020)
This study aimed to (a) quantify the physical workload (P-WL) during training and games throughout the professional rugby season and (b) analyze the influence of the season period and weekly-WL, at short (acute) and moderate (chronic) terms, on physical, biochemical, and psychological responses during the season. Physiological (physical and biochemical) responses to P-WL were analyzed by examining changes in the individual Z score of the Yo-Yo intermittent recovery test (YYIRT), submaximal aerobic tests (5'/5'-test), strength tests, countermovement jump tests, blood sampling, and "recovery-stress" scores (RESTq) in 14 professional players (26.9 ± 1.9 years). Changes throughout the season were analyzed using a linear mixed model to identify changes in P-WL, whereas repeated-measures analysis of variance was used to analyze changes in physiological responses across the season. The relationship between P-WL and physiological responses was analyzed using Pearson's correlation coefficient (r). The results showed that the preseason period comprised the highest level of P-WL compared with all other blocks across the season (p < 0.001). The acute P-WL, acute competitive-WL, and number of impacts seemed to be the WL parameters, which most influenced the physiological responses (changes in testosterone [T], cortisol [C], T/C ratio, IGF-1/C ratio, strength, and RESTq index). The chronic P-WL, particularly conditioning-WL, induced positive changes in fitness characteristics (YYIRT and 5'/5'-test). Finally, this study provides information to players and coaches alike as to the influence of P-WL on as well as adaptations in physiological and psychological indices throughout a playing season. This information can greatly inform the training and preparation of future players in different levels.